2020
DOI: 10.1155/2020/5972594
|View full text |Cite
|
Sign up to set email alerts
|

Holistic View on Cell Survival and DNA Damage: How Model-Based Data Analysis Supports Exploration of Dynamics in Biological Systems

Abstract: In this work, a method is established to calibrate a model that describes the basic dynamics of DNA damage and repair. The model can be used to extend planning for radiotherapy and hyperthermia in order to include the biological effects. In contrast to “syntactic” models (e.g., describing molecular kinetics), the model used here describes radiobiological semantics, resulting in a more powerful model but also in a far more challenging calibration. Model calibration is attempted from clonogenic assay dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Moreover, we have shown by clonogenic assay that CRCE decreased the proliferation ability of viable cells. This also suggests that the proliferation ability might have been impaired by DNA damage, while we cannot rule out the possibility that the cytotoxic effect of CRCE impaired the seeded cells' viability [46]. We assume that the activity of CRCE is exerted via different pathways, which still need to be explored, as both the increase in sub-G 1 and Annexin V/PI assays confirmed that CRCE induces apoptosis and that cell cycle arrest is an intermediate step prior to apoptotic death.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, we have shown by clonogenic assay that CRCE decreased the proliferation ability of viable cells. This also suggests that the proliferation ability might have been impaired by DNA damage, while we cannot rule out the possibility that the cytotoxic effect of CRCE impaired the seeded cells' viability [46]. We assume that the activity of CRCE is exerted via different pathways, which still need to be explored, as both the increase in sub-G 1 and Annexin V/PI assays confirmed that CRCE induces apoptosis and that cell cycle arrest is an intermediate step prior to apoptotic death.…”
Section: Discussionmentioning
confidence: 88%
“…Since the state variable N 0 is tracking clonogenic cells, the MHR model can be used to fit experimental cell survival curves. Although good quality fits of cell survival curves were obtained, unambiguous interpretation of the results can be quite challenging, since very different sets of parameters, representing very different repair dynamics, can fit a set of experimental results almost equally well [57,58]. Furthermore, sometimes unexpected parameter values were found; calibration and validation of the model are thus quite challenging.…”
Section: The Multi-hit Repair Modelmentioning
confidence: 99%
“…Since the MHR model has 8 free parameters and clonogenic assays typically have only 5 data points, additional data are needed for reliable model calibration. To this end, Weyland et al implemented methods to map the model to comet assay readouts to be combined with clonogenic assay data [58]. Results showed that unambiguous model parameters can only be obtained by combining information from both assays in a holistic approach.…”
Section: The Multi-hit Repair Modelmentioning
confidence: 99%
See 1 more Smart Citation